RESTRUCTURING NURSING CARE METHODOLOGY IN A TEACHING HOSPITAL - STATUS REPORT ON EXPERIENCE - Gisele Grespan Suarez; Leomar Albini; Maria Luiza Hexsel Segui; Temis Mary Stefanini Hellberger (Universidade Federal do Paraná, 2000)
The objective of the Commission for Restructuring of the Methodology for Nursing Care (COREMCE), in Parana University Hospital, is to restructure Nursing methodology, guiding that to human care and quality principles. In order to achieve that, several activities were conducted, such as: (1) study of timing and movement with the nursing staff in a teaching hospital: (2) identification of the meaning of care/carer from the perpective of the client attended by the institution; (3) meetings with nurses to reflect on professional practice; (4) nursing records: setting standards for those and establishing the minimum amount of information required on the records form for in-patients and patients in ambulatory treatment; (5) definition of a set of care routines, protocols and standards for the nursing services (6) evaluation of planned activities. We believe that the nursing assistance situation requires restructuring of the nurse´s essencial functions and working routines as the base for the implementation of care methodology according to COREMCE´s objectives.